The Development of Metacognitive Skills-Based Teaching Materials - Mas'ud Mas'ud; Arifin Ahmad; Nurdin Arsyad (Intelektual Pustaka Media Utama, 2018)
It is necessary to develop metacognitive skills-based teaching materials to foster mathematical problem-solving abilities. This research is a research and development. Method used for development is based on [1] using four phases: Design, Construction, Testing, Evaluation and Revision. The criteria used to assess the quality of the learning device refer to the material quality criteria proposed by [2], namely: validity, practicality, effectiveness. Subject of trials in this research are 25 students of XI IPA-4 and 25 students of XI IPA-2. Two indicators of this study are metacognitive skills and problem solving. Metacognitive skills are: prediction skills, planning skills, monitoring skills, and evaluation skills. Indicators of problem solving are: understanding the problem, devising a plan, carrying out the plan, and looking back. The data are collected by giving Tests and questionnaires, and through observations. The research instruments are: questionnaire of validation for teaching materials, student questionnaire responses to instructional materials, observation sheet activities of learners, observation sheets of learning implementation and learning management observation sheet. The result of this research is metacognitive skills-based teaching materials are succeeded (fulfilling the criteria of valid, practical, and effective) to emerge students mathematical problem-solving.